Review Alokasi pada Anggaran Belanja Daerah Kota Bandung Tahun Anggaran 2019-2020 - Novia Aisyah Suryana; Sugih Sutrisno Putra; Mia Rosmiati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
In performance-based budgeting, spending reviews are mandatory as a tool to support continuous improvement in budgeting quality, especially during the current C-19 pandemic. The wider impact of the C-19 pandemic has resulted in the government reallocating and refocusing the budget, both revenue and expenditure budgets. Therefore, this study aims to find out how to spend a review in terms of reviewing allocations in the Bandung City APBD for Fiscal Year 2019- 2020. Qualitative descriptive method is the research method used in this study. The data collection techniques were carried out through interviews and documentation. This study also uses data analysis methods according to Miles and Huberman (1984) which consist of data reduction, data display, and conclusion drawing. The results of this study show that within two fiscal years, 2019-2020, the Bandung City Government can make budget savings by an average of 1.013 billion rupiah.